Digitization after a fashion: The art of compromise. (15th December 2016) - Duncan, Alexandra
Abstract : A case study concerning the in-house digitization of a small collection of Central Saint Martins graduate fashion shows. The background of the collection is outlined (VHS and DVD recordings spanning from 1979 to present), as well as the workflow put in place to deal with the technical aspects of recording, cataloguing, processing and archiving an audio-visual collection with minimal budget and staffing.